2020
DOI: 10.1002/cbf.3488
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA‐155 mediates hepatitis B virus replication by reinforcing SOCS1 signalling–induced autophagy

Abstract: As small conserved RNAs without a coding function, microRNAs are expressed in multicellular organisms and contribute to the modulation of multiple cellular reactions, such as viral replication, as well as autophagy. microRNAs can regulate host gene expression and inhibit or reinforce hepatitis B virus (HBV) replication. Hepatic cells express miR-155 noticeably. Consequently, our study explored miR-155 modulation of HBV replication and investigated the potential mechanism involved. miR-155 was inhibited on HBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Various miRNAs can promote HBV replication via different mechanisms. [42][43][44][45] Our previous studies revealed that HBV could target RIG-I and RIG-G and inhibit STAT1 expression by inducing miR-146a expression, impairing the clearance of the virus via the innate immune system. 46,47 By analyzing the global miRNA expression profiles in HBV-associated HCC, it was found that the expression of many miRNAs, such as miR-150 and miR-342-3p, was altered.…”
Section: Hbv and Micrornamentioning
confidence: 99%
“…Various miRNAs can promote HBV replication via different mechanisms. [42][43][44][45] Our previous studies revealed that HBV could target RIG-I and RIG-G and inhibit STAT1 expression by inducing miR-146a expression, impairing the clearance of the virus via the innate immune system. 46,47 By analyzing the global miRNA expression profiles in HBV-associated HCC, it was found that the expression of many miRNAs, such as miR-150 and miR-342-3p, was altered.…”
Section: Hbv and Micrornamentioning
confidence: 99%
“…Socs1 is an important target gene of microrna-155 according to numerous previous studies (43,44). However, its functions in microvascular endothelial cells and VSMcs remain poorly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of autophagy has been associated with many miRNAs including miR-146a-5p[ 178 ], the miR-99 family[ 179 ] and miR-192-3p, which is downregulated by HBx[ 180 ]. miR-155 has also been implicated in autophagy; however, this miRNA is downregulated following HBV infection[ 181 ]. HBV upregulates expression of miR-192-5p and miR-215-5p, which results in downregulation of apoptosis[ 182 ].…”
Section: Regulatory Noncoding Rnasmentioning
confidence: 99%